1971
DOI: 10.1136/ard.30.3.303
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of adjuvant-induced arthritis in the rat by gold sodium thiomalate.

Abstract: Gold salts have been used in the treatment of rheumatoid arthritis for nearly 40 years. Their effectiveness, while not consistent, has been well established (Freyberg, 1966) and their use continues. Recently, conflicting results concerning the effectiveness of gold salts on adjuvant arthritis in rats have been reported (Newbould, 1963;Jessop and Currey, 1968). Adjuvant arthritis, a crippling deformity resulting from diffuse connective tissue involvement, is considered by some authorities to be the best availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

1973
1973
1991
1991

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…This is mainly because the rat model is suppressed by numerous drugs used in the treatment of the human disease, as for example glucocorticoids, salicylates and other analgesics (Newbould, 1963;Winter & Nuss, 1966;Graeme, Fabry & Sigg, 1966), and immunosuppressive agents (Ward, Cloud, Krawitt & Jones, 1964). However, reports that gold salts improve adjuvant arthritis (Newbould, 1963;Walz, Di Martino & Misher, 1971) were not confirmed by Jessop & Currey (1968).…”
Section: Discussionmentioning
confidence: 98%
“…This is mainly because the rat model is suppressed by numerous drugs used in the treatment of the human disease, as for example glucocorticoids, salicylates and other analgesics (Newbould, 1963;Winter & Nuss, 1966;Graeme, Fabry & Sigg, 1966), and immunosuppressive agents (Ward, Cloud, Krawitt & Jones, 1964). However, reports that gold salts improve adjuvant arthritis (Newbould, 1963;Walz, Di Martino & Misher, 1971) were not confirmed by Jessop & Currey (1968).…”
Section: Discussionmentioning
confidence: 98%
“…Adjuvant-induced edematous response or polyarthritis is the most frequently investigated chronic inflammatory model and is extensively used in rats by pathologists and pharmacologists (Walz et al, 1971). Since Freund's complete adjuvant-induced edematous formation produced a local inflamed swelling which reaches its maximal response during the 4-5 days.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies on the histopathology (19)(20)(21)(22) and on the response to antiinflammatory and immunosuppressive drugs (14, [23][24][25][26] revealed close similarities between this experimental disease and rheumatoid arthritis. It is generally accepted that adjuvant arthritis is an immunologic disease, even though the precise responsible immunogen has not been clearly established (3,6,27).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that modification of adjuvant arthritis as a result of immunosuppression can be differentiated from that due to antiinflammatory effects by varying the drug dosing regimen (25,26). A course of 12 daily doses of immunosuppressive drugs (azathioprine 30 mg/kg PO, cyclophosphamide 10 mg/kg PO), beginning on the day of adjuvant injection was reported by Perper et a1 (26) to prevent the development of the secondary lesions measured on day 21.…”
Section: Discussionmentioning
confidence: 99%